2016
DOI: 10.1080/14737175.2016.1202763
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of disease activity in multiple sclerosis patients

Abstract: Multiple Sclerosis is a chronic inflammatory demyelinating disease that affects 2.5 million people in the world. NEDA (No evidence of disease Activity) -4 is a new concept related to absence of disease activity in the context of MS. It takes into account the following four parameters: relapses; disability progression; lesion load and brain atrophy. Areas covered: The purpose of this paper is to visit the new emerging concepts of NEDA. Although it is considered important and attractive, there is a lack of unifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Several studies have shown that natalizumab is effective in reducing markers of physical disability (EDSS), cognitive decline (SDMT), and various MRI markers of disease activity (Gadolinium (Gd)-enhancing lesions, T2 lesions, brain atrophy) [1113]. There is little if any information regarding the effects of natalizumab on the OCT surrogate marker of disease activity in MS. More recently, the effectiveness of MS treatments have been gauged by using another composite metric known as no evidence of disease activity (NEDA), which usually includes no progression on EDSS scores, lack of any new MRI activity (new contrast enhancing lesions and new or enlarging T2 lesions), and lack of any relapses [14,15]. This 3-component metric is referred to as NEDA-3.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that natalizumab is effective in reducing markers of physical disability (EDSS), cognitive decline (SDMT), and various MRI markers of disease activity (Gadolinium (Gd)-enhancing lesions, T2 lesions, brain atrophy) [1113]. There is little if any information regarding the effects of natalizumab on the OCT surrogate marker of disease activity in MS. More recently, the effectiveness of MS treatments have been gauged by using another composite metric known as no evidence of disease activity (NEDA), which usually includes no progression on EDSS scores, lack of any new MRI activity (new contrast enhancing lesions and new or enlarging T2 lesions), and lack of any relapses [14,15]. This 3-component metric is referred to as NEDA-3.…”
Section: Introductionmentioning
confidence: 99%
“…"No evidence of disease activity (NEDA)" status has emerged as a composite measure of RRMS treatment success and is defined as "no evidence of relapse," "no evidence of disability progression," and "no MRI activity, namely absence of new or enlarging T2 lesions or Gd-enhancing lesions" (Matta et al 2016). NEDA is used as a primary endpoint in AHSCT.…”
Section: Follow-up and Outcomementioning
confidence: 99%
“…No evidence of disease activity (NEDA), defined as the absence of clinical relapses, disability progression, and MRI evidence of active disease, has been proposed as a treatment objective for adult-onset MS. 49 While it may be a good ideal to strive for attaining this target, maintaining a reasonable risk-benefit ratio may also be difficult in some patients. Treatment optimization is therefore often a compromise between long-term safety and what constitutes tolerable levels of disease activity.…”
Section: Therapy Goalsmentioning
confidence: 99%